Ascorbic acid supplementation attenuates schizophrenia‐like symptoms in an animal model induced by ketamine. Issue 1 (29th November 2020) - Supp, Angelo D.; Avila, Silvio; Mastella, Gustavo A.; Damásio, Louyse; de Oliveira, Isabela H.; Godoi, Amanda K.; Michels, Alander; Schuck, Patricia F.; Zugno, Alexandra I.
Abstract: Schizophrenia is a chronic neuropsychiatric disorder with a poorly understood pathophysiology. The theories about the disorder are mainly about dysregulation in one or more systems of neurotransmitters, and the progression triggers the presence of inflammatory markers indicates the possibility that the disorder is initially an inflammatory disease. The objective was to evaluate the ascorbic acid supplementation in an animal model of schizophrenia, on behavioral parameters, and cytokines involved in inflammation IL‐1β, IL‐10. Wistar rats with 60 days of age were used which were supplemented with ascorbic acid at 0.1, 1, and 10 mg/kg or saline for 14 days via orogastric gavage. Subsequently, four groups were given ketamine (25 mg/kg) and four groups received intraperitoneal saline from the 9th‐15th day of the experiment. After 30 min of the last administration of ketamine/saline, and behavioral test, rats were killed by guillotine decapitation and the brain structures were carefully dissected for biochemical analysis. Results showed that ascorbic acid supplementation prevented motor sensory loss but nor alter other parameters evaluated. We concluded that ascorbic acid may be used as a therapeutic adjuvant in schizophrenia and may help to improve the schizophrenic patient's life quality. Abstract : The aim was to evaluate the ascorbic acid supplementation in an animal model of schizophrenia, on behavioral parameters, and cytokines involved in inflammation IL‐1β, IL‐10. The results showed that ascorbic acid supplementation prevented the loss of motor sensory function but nor alter other parameters evaluated. We concluded that ascorbic acid may be used as a therapeutic adjuvant in schizophrenia and may help to improve the schizophrenic patient's life quality.